Ecology and habitat suitability of Cape mountain zebra (Equus zebra zebra) in the Western Cape, South Africa - Olivier, Adriaan Jacobus (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.